Antigenic Relationship of N2-Fixing Pseudomonas Strain H8 to Various Known Cultures and Rice Rhizosphere Isolates Studied By Indirect Enzyme-Linked Immunosorbent Assay (ELISA) - Barraquio, W.L.; Ladha, J.K.; Yao, H.Q.; Watanabe, I. (Canadian Science Publishing, 1986)
The serological relationship of several, mainly Gram-negative, bacteria including type cultures and previously isolated rhizosphere bacteria, to Pseudomonas sp. strain H8, a N2-fixing rhizosphere isolate from Maahas soil, was examined by indirect enzyme-linked immunosorbent assay. None cross-reacted significantly with H8 antibody except some of those rhizosphere bacteria previously found cross-reactive by fluorescent antibody test. Several new rhizosphere isolates from wetland rice grown in various fields showed significant immunoreactivity, and most of the reactive bacteria reduced acetylene. However, the cultural characteristics and acetylene reduction activity of most of these isolates were different from those of H8. None of the rhizosphere isolates from dryland rice cross-reacted. In a pot experiment, bacterial cultures similar to H8 were found only in Maahas soil, but none reacted with antibodies against strains H8 and KLH76 (another N2-fixing pseudomonad from rice root). Other isolates showing reaction with these antibodies were, however, neither culturally similar to these strains nor N2 fixing. The data suggest that Pseudomonas sp. H8 is not distributed widely in soils other than that from which it was originally isolated.